DIFFERENCES IN MOTORIC ABILITIES OF MOTOR SICCESSFUL AND UNSUCCESSFUL ADOLESCENT HANDBALL PLAYERS - Borislav Samardžić; Slavica Bjeljac (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The research has been conducted in January of 2010. on the adequate sample of 90 cadet handball players of 3 handball teams from the Serbian Republic territory. The main goal of the research has been to identify structural differences in basic motor abilities of situationally motor successful and unsuccessful 15-16 year-old players. The measure instrument battery of 10 basic motor variables and 6 evaluation situation-motor success examinees variables has been applied. After the normalization and descriptive statistics for all the variables, the achieved results have been processed by the variance analysis (ANOVA\MANOVA). By the application of the given mathematic-statistical methods the significant differentiation on the level (p<0.01) has been determined, in the analyzed system variable, which project hypothetically latent dimensions: speed and explosive force of jump up, agility, leg movement frequentation, repetitive torso force and aero-anaerobe endurance; while in variables, which are used for factor explosive force jerk, flexibility and arm motion frequency evaluation, hasn't been manifested any statistically significant discrimination. According to the arguments authors interpret achieved results, suggesting the findings implementation in the training of the handball adolescent players processes and the further researching of the tested model